Effects of the Sous Vide and Conventional Electric Oven Cooking Methods on the Physio-Sensory Quality Attributes of Arabian Camel (Camelus dromedarius) Meat - Hobani, Ali I.; Othman, Moath B.; Fickak, Adil A.; Suliman, Gamaleldin M. (Processes, 2023)
This study aimed to evaluate the effect of the sous vide and electric oven cooking methods on the physical and sensory characteristics of camel meat. A combination of 4 cooking temperatures (70, 80, 90, and 100 °C) and 6 cooking times (30, 60, 90, 120, 150, and 180 min) was applied. Both methods significantly affected the meat’s physical properties (pH, cooking loss, density, lightness, redness, and yellowness color components), except for water activity. Furthermore, the cooking temperature and time significantly affected all the sensory properties (tenderness, flavor, juiciness, and general acceptance). The cooking loss was the only parameter affected significantly by the interaction of the cooking method, cooking temperature, and cooking time. It is concluded that the sous vide method is the more suitable method for cooking camel meat compared to the electric oven method considering the cooking temperature and time. Further studies are recommended to estimate energy consumption for both cooking methods evaluated in this study aiming at reducing the overall power expenditure.